Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
After a long period of often frivolous form making and unprincipled egoism in architecture, which have played into the hands of the most venal interests of real-estate developers and marketers, some architects are looking for more substantial ideas to serve, more meaningful goals to strive for, and the manifesto has come back. It is probably a temporary aberration, owing to an unsustainable idealism that lurks within statements of principle, but even their brief resurgence can help to regenerate – at least for a while – our beloved, beleaguered field. (Woods, 2011)